PENERAPAN CORPORATE GOVERNANCE INDEX TERHADAP NILAI PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN - M. Riduan Abdillah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, This research aims to examine the effect of the implementation of Corporate Governance Index (CGI) on corporate value and company growth. The population in this research are all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016. Sampling research using purposive sampling method. The independent variable in this research is the application of Corporate Governance Index (CGI) Siagian et.al (2013) and the dependent variable of this research is the company value measured by price to book value Siagian et.al (2013) and the growth of the company is measured by asset growth Kustono (2009). The results of the research found evidence that the implementation of Corporate Governance Index (CGI) has a significant effect on firm value. The implementation of Corporate Governance Index (CGI) has no significant effect on company growth.